Penerapan Model Self-regulated Learning untuk Meningkatkan Kemandirian Belajar Siswa - Debby Pratama Nugraha; Halimah Sadiyah; Suratno Suratno; Sudaryono Sudaryono; Sri Nurnaningsih; Masrukhin Masrukhin (JURNAL ILMIAH RESEARCH STUDENT, 2025)
Students' learning independence in the learning process is a key factor in building a strong academic foundation and valuable life skills. One learning model that can foster this ability is the self-regulated learning model. The purpose of this study is to describe the steps, strengths, and weaknesses of implementing the self-regulated learning model in Religious Education at Madrasah Tsanawiyah Negeri 4, Klaten Regency. This research employs a qualitative approach. The subjects of this study are teachers at Madrasah Tsanawiyah Negeri 4 Klaten and Madrasah Tsanawiyah Negeri 5 Karanganyar, with the informant being the Religious Education teacher. Data collection techniques include interviews, observations, and documentation. The results of the study are as follows: 1)The steps of the self-regulated learning model include: Analyze, Plan, Implement, Comprehend, Problem Solving, Evaluate, and Modify; 2) The strengths of the self-regulated learning model include: the ability to clarify students’ learning goals, the ability to adjust learning materials according to students’ talents and interests, the ability to create a challenging, stimulating, and enjoyable educational experience, and the ability to avoid uncertain pressures, such as fearful, disappointing, or confusing environments; 3) The weaknesses of the self-regulated learning model include: a tendency for reduced student interaction, the possibility that students may struggle to complete complex independent tasks, and the high demands of self-regulation that are difficult to achieve at a higher level. The conclusion of this study is that the self-regulated learning model can be applied in the learning process as an effort to improve students' learning independence during the learning process at the Madrasah.